Characterization of Light Weight Composite Panels for Table Tennis Table - Mohamad R., M. Yasin (Penerbit Universiti Malaysia Pahang, 2014)
Light weight composite panels (LWCPs) have attracted interest in various applications such as in building and transportation sectors. However, their usage in constructing sports equipment has not been fully explored due to the novelty of the materials and, sometimes, cost or manufacturing issues. Although traditional table tennis tables (TTT) have shown consistent performance, but due to the weight of the materials, commonly medium density fibreboards (MDF) used, the table movability is often limited. In this study, various composite panels using wood veneers and fibre reinforced polymers as face sheets incorporating different core structures have been developed for the purpose of prototyping a full-size standard TTT. In order to comply with the international standard for such a piece of sports equipment, the effects of various material parameters on the coefficient of restitution have been investigated. Such parameters include the types of core material and configuration, the types of face sheet and its thickness. From the study, the composite surfaces have displayed better restitution properties, i.e. bounce of ball is better, compared to the veneer surfaces. The bounce behaviour of the ball is also much closer to that on the standard TTT made from MDF. The findings from this study have demonstrated the potential of using LWCPs for the construction of TTTs to improve the mobility of this sport without compromising the quality of play.